Influence of the Triglyceride-Glucose Index on Adverse Cardiovascular and Cerebrovascular Events in Prediabetic Patients With Acute Coronary Syndrome - Guo, Qianyun; Feng, Xunxun; Zhang, Bin; Zhai, Guangyao; Yang, Jiaqi; Liu, Yang; Liu, Yuyang; Shi, Dongmei; Zhou, Yujie (Frontiers in Endocrinology, 2022)
Abstract Background: Cardiovascular disease and insulin resistance are closely related. The triglyceride-glucose (TyG) index is frequently used as an indicator of insulin resistance. However, there is scant information on the TyG index in the prediabetic population, nor is the prognostic significance of the index known for prediabetes and acute coronary syndrome (ACS) patients. Methods: The clinical endpoint was a major adverse cardiovascular and cerebrovascular event (MACCEs), including cardiac-related death, non-fatal myocardial infarction, ischemia-driven revascularization, and stroke. The TyG index was calculated as = ln [(triglyceride level, mg/dL) × (glucose level, mg/dL)÷2] under fasting conditions. Results: The study included 2,030 prediabetic patients with ACS. Patients were followed up for 2.5 years, during which the total incidence of MACCEs was 12%. After adjustment for covariates, the TyG index was found to be predictive of prediabetes with ACS (HR 4.942, 95%CI: 3.432-6.115, P<0.001). Using propensity score matching, 574 pairs were successfully matched, and the two groups were analyzed in terms of survival. This showed that there was a significantly greater incidence of MACCEs in patients with high TyG indices (HR 3.526, 95%CI: 2.618-4.749, P<0.001), mainly due to ischemia-driven revascularization and stroke. Conclusions: The TyG index independently predicts future MACCEs and may be an important prognostic indicator for patients with prediabetes and ACS.